PENGARUH PENGELOLAAN KEUANGAN DAN PENGGUNAAN P2P LENDING TERHADAP MODAL USAHA SERTA KINERJA KEUANGAN UMKM MAKASSAR - Musdalifa Musdalifa; Ifayani Haanurat; Nasrullah Nasrullah (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
This study uses a survey approach that involves theory, empirical evidence, facts and existing facts with an emphasis on finding a structural model (path) of the relationship between the variables studied. The type of research used is field research (field research). With 100 owners of UKM Makassar City as respondents.The results of this study found that financial management and the use of p2p lending had a significant effect on business capital. However, financial management and the use of p2p lending have no significant effect on financial performance because of the mediating business capital. Thus, it can be concluded that financial management and the use of p2p lending affect the financial performance of SMEs with fully mediated venture capital.Keywords: Financial management, p2p lending, venture capital, financial performance and UMKM.